1996
DOI: 10.1001/archpsyc.1996.01830070053009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Brain Magnetic Resonance Imaging in Attention-Deficit Hyperactivity Disorder

Abstract: This first comprehensive morphometric analysis is consistent with hypothesized dysfunction of right-sided prefrontal-striatal systems in ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

57
631
9
32

Year Published

1996
1996
2010
2010

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,001 publications
(729 citation statements)
references
References 92 publications
57
631
9
32
Order By: Relevance
“…In support of the role for frontal cortex in ADHDlike behaviors, lesions of the frontal lobes cause a breakdown of goal directed activity, executive function, attention and produce hyperactivity (Benson and Stuss 1982;Petrides and Milner 1982). In imaging studies, the right frontal lobes including PFC (Hynd et al 1990;Castellanos et al 1996b) and the caudate nucleus of children with ADHD were smaller in volume than controls, possibly suggesting a neurodevelopmental lag in the maturation of the associated neuronal pathways and their connectivity (Castellanos et al 1996b). Thus, increasing catecholaminergic neurotransmission in cortical areas may be involved in the efficacy of psychostimulants and atomoxetine in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…In support of the role for frontal cortex in ADHDlike behaviors, lesions of the frontal lobes cause a breakdown of goal directed activity, executive function, attention and produce hyperactivity (Benson and Stuss 1982;Petrides and Milner 1982). In imaging studies, the right frontal lobes including PFC (Hynd et al 1990;Castellanos et al 1996b) and the caudate nucleus of children with ADHD were smaller in volume than controls, possibly suggesting a neurodevelopmental lag in the maturation of the associated neuronal pathways and their connectivity (Castellanos et al 1996b). Thus, increasing catecholaminergic neurotransmission in cortical areas may be involved in the efficacy of psychostimulants and atomoxetine in ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…The results of diverse studies of the anatomic features of the caudate in ADHD patients have been contradictory. Some studies have reported that the right caudate nucleus is smaller in children with ADHD, 4,[15][16][17] whereas others have found that only the left caudate is smaller in ADHD individuals 5 or that there is no difference. 18 Another study found that the total volume of the caudate was smaller in individuals with ADHD but that this difference disappeared during adolescence.…”
Section: Introductionmentioning
confidence: 98%
“…Methylphenidate (MPH) blocks the dopamine and norepinephrine transporters (Castellanos, 1997). Furthermore, neuroimaging studies have consistently reported abnormalities in nigrostriatal dopaminergic brain structures (Aylward et al, 1996;Castellanos et al, 1996) and function (Zametkin et al, 1993;Vaidya et al, 1998;Zametkin and Liotta, 1998) in children with ADHD. Consistent with these findings, neuroimaging studies in ADHD adults have shown alterations in presynaptic dopamine storage processes (Ernst et al, 1998) and in the density of striatal dopamine transporters (DATs) (Dougherty et al, 1999;Krause et al, 2000Krause et al, , 2002, although not consistently.…”
Section: Introductionmentioning
confidence: 99%